Interleukin 27, like interferons, activates JAK-STAT signaling and promotes pro-inflammatory and antiviral states that interfere with dengue and chikungunya viruses replication in human macrophages - Valdés-López, Juan Felipe; Hernández-Sarmiento, Lady Johana; Tamayo-Molina, Y. S.; Velilla-Hernández, Paula A.; Rodenhuis-Zybert, Izabela A.; Urcuqui-Inchima, Silvio (Frontiers in Immunology, 2024)
Interferons (IFNs) are a family of cytokines that activate the JAK-STAT signaling pathway to induce an antiviral state in cells. Interleukin 27 (IL-27) is a member of the IL-6 and/or IL-12 family that elicits both pro-and anti-inflammatory responses. Recent studies have reported that IL-27 also induces a robust antiviral response against diverse viruses, both in vitro and in vivo, suggesting that IFNs and IL-27 share many similarities at the functional level. However, it is still unknown how similar or different IFN-and IL-27-dependent signaling pathways are. To address this question, we conducted a comparative analysis of the transcriptomic profiles of human monocyte-derived macrophages (MDMs) exposed to IL-27 and those exposed to recombinant human IFN-α, IFN-γ, and IFN-λ.We utilized bioinformatics approaches to identify common differentially expressed genes between the different transcriptomes. To verify the accuracy of this approach, we used RT-qPCR, ELISA, flow cytometry, and microarrays data. We found that IFNs and IL-27 induce transcriptional changes in several genes, including those involved in JAK-STAT signaling, and induce shared pro-inflammatory and antiviral pathways in MDMs, leading to the common and unique expression of inflammatory factors and IFN-stimulated genes (ISGs). Importantly, the ability of IL-27 to induce those responses is independent of IFN induction and cellular lineage.Additionally, functional analysis demonstrated that like IFNs, IL-27-mediated response reduced chikungunya and dengue viruses replication in MDMs. In summary, IL-27 exhibits properties similar to those of all three types of human IFN, including the ability to stimulate a protective antiviral response. Given this similarity, we propose that IL-27 could be classified as a distinct type of IFN, possibly categorized as IFN-pi (IFN-π), the type V IFN (IFN-V).